Prediction of nutritive intake energy and substrates of Czech pregnant women - Hronek, Miloslav; Doubkova, Pavlina; Tosner, Jindřich; Zadak, Zdenek (Nutrition, 2011)
OBJECTIVE: Equations linking nutritional intake of energy and substrates (NIES) to anthropometry during pregnancy are currently unknown. The aim of this longitudinal study was to determine the predictive equations for NIES as an expression of dietary patterns. METHODS: In total, 152 randomly recruited healthy pregnant Czech women (non-smokers, non-users of long-term medications or abusers of alcohol or drugs, normoglycemic, euthyroid, and non-anemic) were divided into two cohorts: group 1 (n = 31) was used for the determination of equations for NIES during pregnancy, and group 2 (n = 121) for cross-validation of these equations. In both study groups, anthropometry was measured and resting energy expenditure obtained by indirect calorimetry after 12 h of fasting during four phases of pregnancy. NIES was evaluated from self-reported dietary intake records over 7 d. RESULTS: Strong relations were found between NIES and anthropometric parameters, especially the difference between pregnancy body weight and ideal body weight. By correlation analysis and linear regression, new predictive equations were derived for NIES during pregnancy using the difference between pregnancy body weight and ideal body weight. A high concordance was observed between values from the predictive equations and the actual assessed values of NIES in group 2. CONCLUSION: The proposed equations for nutritional intake of energy, protein, and fats have a reasonable prediction power during pregnancy in relation to physiologic birth outcome.
Keywords: energetický metabolismus; Maternal Nutritional Physiological Phenomena; nutriční stav; longitudinální studie; nepřímá kalorimetrie; fyziologie výživy v mateřství; Česká republika; hodnocení stavu výživy; Nutrition Assessment; Pregnancy; těhotenství; Adult; dospělí; antropometrie; lineární modely; Calorimetry, Indirect; Rest; Body Weight; odpočinek; Czech Republic; Anthropometry; lidé; Energy Metabolism; ženské pohlaví; Humans; Energy Intake; Linear Models; Nutritional Status; Longitudinal Studies; energetický příjem; Female; tělesná hmotnost